A Comparative Study between Autologous Dural Closure versus Collagen Matrix (DuraGen) Closure in Decompressive Craniectomy for Trauma - Barooah, Rajesh Kumar; Baishya, Basanta Kumar; Haloi, Hriday; Bhuyan, Mrinal; Ali, Asman; Sarma, Kishore (Indian Journal of Neurotrauma, 2020)
Introduction Neurosurgeons often deal with the problem of a complete and watertight dural closure after cerebral operative procedures. In decompressive craniectomy done for trauma, autologous grafts such as galea, temporalis fascia can be time consuming. Hence this study was undertaken to look into the outcome using collagen matrix graft for dural closure.Aims and Objectives To study the difference between autologous dural graft closure and collagen matrix graft with respect to the time taken for closure, cerebrospinal fluid (CSF) leakage, and wound infection.Methods This prospective study includes 30 patients who underwent decompressive craniectomy for trauma. Duraplasty with temporalis fascia graft and nonautologous collagen matrix dural patch was done by randomization. Specific time points during craniectomy and cranioplasty was calculated. Total time for the procedures and the time for dural repair and separation was calculated.Results The use of collagen matrix in decompressive craniectomy resulted in decrease in mean operative time during the first surgery by average 45 minutes (p< 0.5) as compared to the use of autologous graft. There is reduction in the operating time during second surgery (cranioplasty) by 35 minutes (p< 0.5). The patients using collagen matrix graft did not record any CSF leakage or wound infection. Excellent uptake of the collagen by the duramater was seen.Conclusion The use of collagen to cover the dural defect for decompressive craniectomy for trauma results in significant reduction in the operating time during the first surgery and also in cranioplasty. There is reduction in CSF leakage and hence duration of hospital stay and cost.
Keywords: dural closure; collagen matrix graft; craniectomy